Assessment of Clinical Characteristics and Mortality-Associated Factors in COVID-19 Critical Cases in Kuwait - Ayed, Mariam (Med Princ Pract, 2021)
OBJECTIVE: The objective of this study was to assess the clinical characteristics and identify mortality risk factors in intensive care unit (ICU)-admitted COVID-19 patients. METHODS: We recruited and analyzed SARS-CoV-2-infected adult patients (age ≥18 years) who were admitted to the ICU at Jaber Al-Ahmad Al Sabah Hospital, Kuwait, between March 1, 2020, and April 30, 2020. The risk factors associated with in-hospital mortality were assessed using multiple regression analysis. RESULTS: We recruited a total of 103 ICU patients in this retrospective cohort. The median age of the patients was 53 years and the fatality rate was 45.6%; majority (85.5%) were males and 37% patients had more than 2 comorbidities. Preexisting hypertension, moderate/severe acute respiratory distress syndrome, lymphocyte count <0.5 × 109, serum albumin <22 g/L, procalcitonin >0.2 ng/mL, D-dimer >1,200 ng/mL, and the need for continuous renal replacement therapy were significantly associated with mortality. CONCLUSION: This study describes the clinical characteristics and risk factors for mortality among ICU patients with COVID-19. Early identification of risk factors for mortality might help improve outcomes.